Effect of maceration time on characteristics of acid-hydrolyzed cellulose from pineapple leaf - Abu Kassim, Naziratulasikin (2018)
Recently, the utilisation of other non-wood materials as well as crop residues have attracted global attention due to their environmentally friendly and feasible properties once becomes a product. Pineapple leaf is a residue of fresh fruit for domestic used and canned pineapple industry. This residue was produced in large scale quantities and relatively inexpensive source. Pineapple leaf can be utilised as a potential source of isolating cellulose in micro and nano scale dimensions of cellulose. In order to attain such celluloses, some pre-treatment and acid hydrolysis process was performed in controlled conditions. The chlorinated solvents were widely consumed in certain industries to produce high purity of cellulose, though chlorine is toxic and harmful to environment. Maceration approach was introduced to overcome the increasing of environment concern. Hence, the aim of this study was to isolate cellulose by introducing maceration method via hydrogen peroxide and acetic acid at 80°C. This treatment also plays with variables of maceration duration (TF-2, TF-3, and TF-4) to get the best results of obtained cellulose. The process for the acid-hydrolyzed part comprising the macerated cellulose to further on acid hydrolysis process by considered some factors such as acid concentration, temperature, hydrolysis time, and pulp-to-acid ratio. The macerated cellulose was treated with 64 %w/w of sulfuric acid, 45 °C temperature, 45 min and 60 min (for TF-4) of hydrolysis time, 1:30 of pulp-to-acid ratio, and 20 minutes of sonication time. Resultant cellulose was tested for chemical composition, morphological observation, thermogravimetric analysis, Fourier Transform Infrared spectroscopy analysis, and crystallinity index. It was shown that the best maceration treatment was TF-3 (3 hours maceration time) and followed by TF-2 and TF-4 by considering its cellulose composition. By conducting maceration treatment, results revealed that pineapple leaf for TF-3 has cellulose content which is 70.92%. Results also demonstrated that mainly hemicellulose and residual lignin remains after the maceration treatment. It was expected because maceration treatment was used. Maceration treatment also has been found successfully decreased macerated cellulose diameter and length. Prior to acid hydrolysis treatment, the decreasing of acid-hydrolyzed diameter was attained. The lowest diameter for acid-hydrolyzed cellulose was 111.6 nm. By performing acid hydrolysis treatment, the crystallinity index for acid-hydrolyzed cellulose was increased. Highest crystallinity index for acid- hydrolyzed cellulose was 69.30% for AC-345 compared to original raw material which is 43.70%. Higher thermal degradation was found in macerated cellulose and acid- hydrolyzed cellulose was 338°C and 337°C, respectively. In conclusion, pineapple leaf was found as potential source of purified cellulose with some modifications needed prior to produce a product or as reinforcement in other materials such as composites field.